Analysis of vaccine losses by temperature changes in a Health Region from Minas Gerais State, Brazil - Simões, Naiara Cristina Silva; Santos, Isabela Flávia dos; Oliveira, Valéria Conceição; Guimarães, Eliete Albano de Azevedo; Andrade, Heuler Souza (ABCS Health Sciences, 2020)
Introduction: Immunobiologicals are of great importance for the prevention and eradication of diseases. However, the lack of maintenance of the cold chain generates several problems related to losses of these substances, burdening an important amount of public resources. Objective: To analyze vaccine losses in a Health Region (Região Ampliada de Saúde Oeste) of Minas Gerais State in Brazil. Methods: This is a descriptive study, based on secondary data obtained through forms used by the regional health agency (Superintendência Regional de Saúde, SRS), to register losses of immunobiologicals due to temperature changes. Forms from February 2016 through January 2018 were analyzed. The data was organized and validated by double typing. Results: Vaccine losses were caused by lack of electrical energy (40.83%), followed by equipment failure (36.67%), and professional error (10%). As a consequence, 17,229 bottles of vaccines (65.78%) were discarded, corresponding to 111,145 doses. The financial loss was R 604,340.31. Conclusion: Losses of vaccines due to temperature changes were relevant in the studied region, damaging the budget for the local health network. Therefore, it is suggested that measures to minimize these losses should be adopted.